Psikologi klinis perkembangan teori, praktik, dan penelitian Norman D.Sundberg, Allen A. Winebarger, Julian R.Taplin; penerjemah, Helly Prajitno Soetjipto, Sri Mulyantini Sietjipto - SUNDBERG, Norman D; Sucipto, Sri Mulyantini; Sucipto, Helly Prayitno; Taplin, Julian R; Winebarger, Allen A (2007)
xii, 565, [2] hlm ilus 28 cm